Prevalence and Demographic Characteristics of Metabolic Syndrome in Iraqi Patients with Acute Coronary Syndrome - AlDaggistany, Zina S.; Ahmed, Ihab S.; Al-Johar, Zuhair A. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: The demographic characteristics of Iraqi patients with metabolic syndrome (MS) and presenting with acute coronary syndrome (ACS) have been scarcely studied before. Aim of the study: To study the socio-demographic characteristics of a group of Iraqi patients with MS presenting with ACS. Patients and Methods: A convenience sample of 150 cases presenting with ACS and admitted to the coronary care unit (CCU) of Al-Yarmouk Teaching Hospital in Baghdad from mid-January through July 2011 were included in the current cross-sectional study. The data needed for the study was collected through a direct interview to fill a questionnaire by all cases carried out by a consultant physician. Results: Of all the 150 ACS cases included in the study, 69.3% had MS. The prevalence of MS among males was 63.8%, and among females was 78.6%. The most frequently seen age group was 50-59 years. Gender differences in MS patients were statistically significant regarding residence (Urban: 63.3% M, 84.1% F), educational level (illiteracy: 15% M, 52.3% F, high education: 25% M, 4.5% F), and employment (Employed: 50% M, 22.7% F). Males with MS and ACS had more myocardial infarction (MI) (80%) than unstable angina, compared to females (41% MI), with statistically significant associations. Conclusion: The prevalence of MS in Iraqi ACS cases is high, and among them MI was significantly higher in males.